2011
DOI: 10.1055/s-0031-1293493
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Brucellosis

Abstract: Brucellosis is a zoonosis of worldwide distribution caused by small gram-negative nonencapsulated coccobacilli of the genus Brucella. It is characterized by a granulomatous reaction in the reticuloendothelial system. Because it affects several organs and tissues, it may have various clinical manifestations. Musculoskeletal involvement is one of the most common locations, and the frequency of bone and joint (osteoarticular) involvement of brucellosis varies between 10% and 85%. Osteoarticular involvement includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 7 publications
1
31
2
4
Order By: Relevance
“…According to various studies, the frequency of osteoarticular complications has been reported in 10 to 80 % of patients (14,15). In a previous study in our region, the frequency of osteoarticular complications was 28.5%, of which 75.7% cases were of sacroiliitis (16).…”
Section: Discussionmentioning
confidence: 72%
“…According to various studies, the frequency of osteoarticular complications has been reported in 10 to 80 % of patients (14,15). In a previous study in our region, the frequency of osteoarticular complications was 28.5%, of which 75.7% cases were of sacroiliitis (16).…”
Section: Discussionmentioning
confidence: 72%
“…The optimal treatment duration has not been clearly established, but at least three to 6-months of treatment is recommended. 2,4 Nevertheless, there is not any standard therapy for osteoarticuler brucellosis. 1,19 In the early phases of the disease, medical treatment could be efficient but in older patients (50-60 years old) it might not provide satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarticular involvement in brucellosis is most commonly encountered as followings: spondylitis, sacroiliitis, osteomyelitis, peripheral arthritis, bursitis, and tenosynovitis. 2 Spinal infection due to brucellosis causes morbidity resulting from infectious disease in the infested regions of the world and particularly in the rural areas including our country. 3 Spondylodiscitis is most commonly seen in the lumbar, cervical and thoracic regions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Spondilit, sakroileit, osteomiyelit, periferal artrit, bursit ve tenosinovit olarak karşımıza çıkabilir. Erişkinlerde en sık sakroileit veya spondilodiskitin, çocuklarda ise en sık monoartiküler artritin (özellikle diz ve kalçada) görüldüğü bildirilmiştir ancak bizim hastamızda spondilodiskit şeklinde tutulum olmuştur (2). Bazı yayınlarda brusellar osteoartiküler komplikasyonların genetik predispozisyonla (HLA-B39 gibi) ilişkili olabileceği belirtilmiş olsa da çoğu çalışmada HLA gruplarıyla ilişki bulunamamıştır (1,3).…”
Section: Discussionunclassified
“…Osteoartikuler bruselloz periferik artrit, sakroileit, spondilit, tenosinovit, bursit ve osteomyelit şeklinde ortaya çıkabilmektedir (2). Burada ateş, bel ağrısı ve skolyoz ile gelen bir hastada klinik şüphe, prozon fenomeninin akla gelmesi ve manyetik rezonans görüntüleme yöntemi ile tanı alan brusellar spondilodiskitli bir olgu sunulmuştur.…”
Section: Introductionunclassified